PENGARUH KETIDAKPASTIAN NILAI PARAMETER TERBANG TERHADAP TITIK JATUH ROKET R-HAN 300 - Ahmad Riyadl; Robertus Heru Triharjanto; Pujo Widodo (ELEMEN : JURNAL TEKNIK MESIN, 2023)
The impact point is the main parameter of the performance of an artillery rocket. During its flight, a rocket experiences uncertainty of some parameter’s value, which is caused by the condition of the rocket when it exits the launcher, the ever-changing atmospheric conditions, and fabrication imperfections. This disturbance will cause deviation on the impact point. This study aims to determine the deviation of the impact point of an artillery rocket due to the value uncertainty of several parameters that affect its flight trajectory, and this analysis will be used as a reference for designers and users in further design processes. Six degrees of freedom simulation calculates the rocket's impact point and deviation. The results showed that to minimize the impact point’s deviation, the quality of the launcher fabrication must be improved, predicting aerodynamics with CFD and firing the rocket at low wind disturbances.